Botryoid odontogenic cyst - Vandana Arya; M Jonathan Daniel (Wolters Kluwer Medknow Publications, 2009)
Botryoid odontogenic cyst is an unusual type of cyst. It was first reported by Weathers and Waldron in 1973. It is simply a polycystic variant of the lateral periodontal cyst developing through cystic transformation of multiple islands of dental lamina rests. A case of botryoid odontogenic cyst in a 35-year -old female patient with its clinical, radiological and histopathological presentation is reported.